Prospects and tasks of sound vision application for diagnostics and visualization of cavitation and turbulent flows in medium and large diameter fittings - Gorobchenko Stanislav; Kovalev Dmitriy; Taraban Maria; Meshkov Sergey; Bedenko Iraida; Sakhapov Rustem (E3S Web of Conferences, 2023)
The possibility of using sound vision to solve the problems of visualization and diagnostics of caviation and turbulent flows arising during the operation of pipeline valves is considered. The available methods of realization of sound vision are analyzed. A block diagram with the reconstruction of a holographic image is proposed. The diagram could visualize the picture of the cavitation flow. It is shown that it is most promising to develop such circuit and technical solutions that could form a complete picture of the flow in dynamics with the ability to digitize it for further analysis.